Role of Hydrogen Evolution during Epitaxial Electrodeposition of Fe on GaAs. Issue 4 (20th December 2017) - Leistner, Karin; Duschek, Kenny; Zehner, Jonas; Yang, Mingze; Petr, Andreas; Nielsch, Kornelius; Kavanagh, Karen L.
Abstract : The electrode reactions during the initial stages of Fe electrodeposition on GaAs from a sulfate-based aqueous electrolyte, were investigated. Electrochemical quartz microbalance measurements were carried out to distinguish hydrogen evolution from Fe deposition. For conditions with a lower hydrogen evolution rate, hemispherical Fe nanoparticles with negligible in-plane magnetic anisotropy are obtained. In contrast, when hydrogen evolution dominates over Fe electrodeposition, the deposited nanoparticles exhibit a defined faceted shape, crystallographic alignment and magnetic in-plane anisotropy. This beneficial impact of hydrogen evolution on the epitaxy is discussed with regard to the role of hydrogen adsorption during Fe/GaAs interface formation.